2010
DOI: 10.21307/ijssis-2017-398
|View full text |Cite
|
Sign up to set email alerts
|

A Spherical Haptic Interface with Unlimited Workspace

Abstract: Abstract-Over the last two decades, various haptic interfaces have been developed. However, their workspace has been mechanically restricted. This limited workspace reduces operationality, because operation should be suspended at the boundary. In this paper, to tackle this problem, a spherical haptic interface is developed, which utilizes a ball as an interface with the human. The ball is driven by three DC motors through omni wheels. Consequently, unlimited workspace is achieved for orientation.Furthermore, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…This section experimentally confirms the characteristics of the ABENICS mechanism mentioned in the introduction, i.e., three RDoF, absence of slippage, and the hypothesis 7 proposed in Section IV-A. Then, the corresponding results and the practical issues of the mechanism are discussed.…”
Section: Experiments and Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This section experimentally confirms the characteristics of the ABENICS mechanism mentioned in the introduction, i.e., three RDoF, absence of slippage, and the hypothesis 7 proposed in Section IV-A. Then, the corresponding results and the practical issues of the mechanism are discussed.…”
Section: Experiments and Discussionsupporting
confidence: 80%
“…This slide is generated when the pole of the MP-gear is directed to the right side of this figure . the material. As the SH-cutter revolves around the material, the structural axis rotates as described by (7). This process is essential for meshing the MP-gear with the CS-gear.…”
Section: ) Monopole Gear (Mp-gear)mentioning
confidence: 99%
See 1 more Smart Citation
“…Effective motor skill training becomes an important issue especially in the area of surgical, handwriting, rehabilitation and tele-operation. Thus, robotic devices 11,12 and haptic interface 13,14 are increasingly being developed and used as tools for training skillful movement. If objective or quantitative feedback can be provided to the trainee each time they train, then, the training will be more effective.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that SR can enhance the detection and transmission of weak signals in certain nonlinear and multi-stable systems by using noise [5][6]. If we can incorporate SR into not only the robotic tactile sensors [7][8] but also haptic displays [9]- [11], they can take advantage of it because tactile sensing accepts the external noise inevitably arising from touching an object surface. Thus, we investigate SR of human tactile sensing in this paper.…”
Section: Introductionmentioning
confidence: 99%